Wedded to prosperity?: informal influence and regional favoritism - Bomprezzi, Pietro; Dreher, Axel; Fuchs, Andreas; Hailer, Teresa; Kammerlander, Andreas; Kaplan, Lennart; Marchesi, Silvia; Masi, Tania; Robert, Charlotte; Unfried, Kerstin (Discussion papers, 2024)
We investigate the informal influence of political leaders' spouses on the subnational allocation of foreign aid. Building new worldwide datasets on personal characteristics of political leaders and their spouses as well as on geocoded development aid projects (including new data on 19 Western donors), we examine whether those regions within recipient countries that include the birthplace of leaders' spouses attract more aid during their partners' time in office. Our findings for the 1990-2020 period suggest that regions including the birthplaces of political leaders' spouses receive substantially more aid from European donors, the United States, and China. We find that more aid goes to spousal regions prior to elections and that developmental outcomes deteriorate rather than improve as a consequence. For Western aid but not for China, these results stand in some contrast to those for leader regions themselves. This suggests that aid from Western donors is directed from serving obvious political motives to promoting more hidden ones.
Keywords: Graue Literatur